(untitled) (Journal of Social Economics Research, 2024)
This study examines the influence of opportunistic managers’ motivation and corporate governance on using fair value measurement for investment properties. It was conducted on a sample of 126 corporations listed on the Indonesia Stock Exchange from 2016 to 2020, using logistic regression and moderated regression analysis. The results showed that opportunistic motivation significantly affects the use of fair value measurement for investment properties. These results provide empirical evidence that fair value measurement, intended to enhance the relevance and reliability of financial reporting, can be leveraged to maximize corporate profits for certain interests. Additionally, the study indicates that corporate governance structure strengthens management’s motivation to utilize fair value for investment properties, contrary to the expected role of corporate governance in mitigating managerial opportunistic behaviour. Future studies could explore alternative measurements, such as the difference in fair value profit/loss, to further support the bonus plan hypothesis in the Positive Accounting Theory framework. The practical implication of this study is to offer an understanding of the rationales behind the choice of accounting policies for investment property. This will enable the development of policies and regulations that safeguard financial statement users from management’s opportunistic motives when selecting accounting methods. In addition, this research can also be evaluation material about opportunistic motivations that management may have in implementing IFRS.